Inhibition of p53 Function Prevents Renin-Angiotensin System Activation and Stretch-Mediated Myocyte Apoptosis - Leri, Annarosa (American Society for Investigative Pathology, 2000)
To determine whether stretch-induced activation of p53 is necessary for the up-regulation of the local renin-angiotensin system and angiotensin II (Ang II)-induced apoptosis, ventricular myocytes were infected with an adenoviral vector carrying mutated p53, Adp53m, before 12 hours of stretch. Noninfected myocytes and myocytes infected with AdLacZ served as controls. Stretching of Adp53m-infected myocytes prevented stimulation of p53 function that conditioned the expression of p53-dependent genes; quantity of angiotensinogen (Aogen), AT(1), and Bax decreased, whereas Bcl-2 increased. Ang II generation was not enhanced by stretch. Conversely, stretch produced opposite changes in noninfected and AdLacZ-infected myocytes: Aogen increased twofold, AT(1) increased 2.1-fold, Bax increased 2.5-fold, and Ang II increased 2.4-fold. These responses were coupled with 4.5-fold up-regulation of wild-type p53. Stretch elicited comparable adaptations in p53-independent genes, in the presence or absence of mutated p53; renin increased threefold, angiotensin-converting enzyme increased ninefold, and AT(2) increased 1.7-fold. Infection with Adp53m inhibited myocyte apoptosis after stretch. Conversely, stretch increased apoptosis by 6.2-fold in myocytes with elevated endogenous wild-type p53. Thus, a competitor of p53 function interfered with both stretch-induced Ang II formation and apoptosis, indicating that p53 is a major modulator of myocyte renin-angiotensin system and cell survival after mechanical deformation.